2010
DOI: 10.1364/oe.18.014395
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive graphene biosensors based on surface plasmon resonance

Abstract: A surface plasmon resonance (SPR) based graphene biosensor is presented. It consists of a graphene sheet coated above a gold thin film, which has been proposed and experimentally fabricated recently [ChemPhysChem 11, 585 (2010)]. The biosensor uses attenuated total reflection (ATR) method to detect the refractive index change near the sensor surface, which is due to the adsorption of biomolecules. Our calculations show that the proposed graphene-on-gold SPR biosensor (with L graphene layers) is (1 + 0.025 L) x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
438
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 859 publications
(476 citation statements)
references
References 18 publications
6
438
0
5
Order By: Relevance
“…Recent studies have shown that graphene can be used as an enhanced SPR substrate for biosensing applications. There are several advantages for using graphene-based SPR substrate for sensing: i) they are able to induce significantly large field enhancement at the substrate interface; ii) graphene has relatively large surface area (~2630 m 2 g -1 ) thus allowing it to have a better surface contact with the analyte; and iii) graphene surface can selectively detect aromatic compounds through pi-stacking force and this will help one to be able to study challenging experiments such as DNA interaction with proteins at extreme dilute condition [22][23][24]. However, it was reported that graphene-based SPR sensors possessed the highest detection sensitivity when the total number of graphene layers deposited on the metallic SPR sensing substrate (50 nm) is larger than 10.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that graphene can be used as an enhanced SPR substrate for biosensing applications. There are several advantages for using graphene-based SPR substrate for sensing: i) they are able to induce significantly large field enhancement at the substrate interface; ii) graphene has relatively large surface area (~2630 m 2 g -1 ) thus allowing it to have a better surface contact with the analyte; and iii) graphene surface can selectively detect aromatic compounds through pi-stacking force and this will help one to be able to study challenging experiments such as DNA interaction with proteins at extreme dilute condition [22][23][24]. However, it was reported that graphene-based SPR sensors possessed the highest detection sensitivity when the total number of graphene layers deposited on the metallic SPR sensing substrate (50 nm) is larger than 10.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was reported that graphene-based SPR sensors possessed the highest detection sensitivity when the total number of graphene layers deposited on the metallic SPR sensing substrate (50 nm) is larger than 10. Even with such thick layers of graphene on the SPR substrate, the sensitivity enhancement factor has only increased from 1.25 to 2, which is considered to be an incremental improvement for the sensitivity of the SPR biosensor [22,[25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…We anticipate that graphene can provide new perspectives in plasmonics in three different ways: (1) as a surface which directly supports surface plasmons at infrared frequencies, 14,16,17 (2) as a tunable transparent platform whose optical properties can be tuned by an external electric field, [18][19][20] and (3) as a functional coating for the existing plasmonic devices. [21][22][23][24][25][26] In this paper, we demonstrate an application of graphene in plasmonics as an example for a functional coating. The primary goal of the paper is to understand the plasmonic properties of graphene coated metal surfaces.…”
mentioning
confidence: 99%
“…This type of SPR sensors have been proposed before but have not been demonstrated yet. 21,22 Particularly, we studied nonspecific adsorption of a serum albumin protein (BSA, bovine serum albumin) on a graphene layer using a microfluidic device integrated with a graphene functionalized SPR sensor.…”
mentioning
confidence: 99%
“…4e). Examples include Wu et al [189], where a change in biomolecule concentration led to a change in refractive index near the metal surface which leads to change in propagation constant of the SPP which can be measured by attenuated total internal reflection. Commercially available sensors based on SPR such as the BIAcore instrument from Pharmacia have been widely used for a number of decades [190][191][192].…”
Section: Existing and Emerging Applicationsmentioning
confidence: 99%